The criminal clause in national jurisprudence - Carrillo Rodríguez, Jorge Luis (2019)
At present there are serious questions about the efficiency of the criminal clause as a compulsory mechanism for compliance and conventional settlement of damages. Due to the fact that the penal clause does not offer any security to the contracting parties, they prefer to use other mechanisms that ensure the fulfillment of their obligations effectively, although they could represent higher costs. In this paper, we examine the functions of the penal clause, as well as its possible reduction and increase.